Analysis of surface roughness of glass-ionomer cements and compomer - Pedrini, Denise [UNESP]; Candido, MSM; Rodrigues, A. L. (Blackwell Publishing, 2003)
The purpose of this study was to evaluate the surface roughness of two glass-ionomer cements (Vitremer and Chelon-Fil), and one compomer (Dyract) when submitted to different finishing/polishing procedures at different times. A hundred 80-sample discs were made of each material and randomly divided into six finishing/polishing groups: mylar strip (control); Sof-Lex discs; diamond burs; diamond burs/Sof-Lex discs; 30-fluted carbide bur; 30-fluted carbide bur/Sof-Lex discs. These procedures were carried out immediately after preparation of the samples, after 24 and 168 h. Average surface roughness (Ra) was measured with a profilometer and the values were compared using anova (P < 0.05). The smoothest surface for all materials was obtained when cured in contact with the mylar strip. All other tested products increased surface roughness of restorative materials, but Sof-lex discs lead to better results. The worst results were verified with diamond burs. The finishing/polishing procedures, when performed immediately, can improve the roughness of glass-ionomer cements but not of the compomer tested.
Keywords: glass-ionomer cements; compomer; surface roughness